2015
DOI: 10.3109/0886022x.2015.1074462
|View full text |Cite
|
Sign up to set email alerts
|

Naringin ameliorates sodium arsenite-induced renal and hepatic toxicity in rats: decisive role of KIM-1, Caspase-3, TGF-β, and TNF-α

Abstract: Chronic exposure of a naturally occurring metal arsenic leads to renal and hepatic diseases. Naringin, a flavanone glycoside, possesses anti-inflammatory and anti-oxidant potential. The aim of this investigation was to evaluate the protective effect of naringin against arsenic-induced renal and hepatic toxicity in rats. Renal and hepatic toxicity was induced in rats by sodium arsenite (5 mg/kg, p.o.). Rats were treated orally with either vehicle or naringin (20, 40, and 80 mg/kg) or Coenzyme Q10 (10 mg/kg) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(52 citation statements)
references
References 114 publications
4
47
1
Order By: Relevance
“…Furthermore, nitric oxide (NO) is an unconventional intracellular messenger in the nervous system and its elevated level associated with sensitized spinal as well as central neurons (Lin et al, 1999[58]). NO reacts with ROS and acts as an oxidant (Adil et al, 2015[4]; Badole et al, 2015[9]; Kamble et al, 2013[36]). Reaction with deficient superoxide dismutase leads to the production of notorious peroxynitrite, which affects any cell molecule (Honmore et al, 2015[29], 2016[30]).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nitric oxide (NO) is an unconventional intracellular messenger in the nervous system and its elevated level associated with sensitized spinal as well as central neurons (Lin et al, 1999[58]). NO reacts with ROS and acts as an oxidant (Adil et al, 2015[4]; Badole et al, 2015[9]; Kamble et al, 2013[36]). Reaction with deficient superoxide dismutase leads to the production of notorious peroxynitrite, which affects any cell molecule (Honmore et al, 2015[29], 2016[30]).…”
Section: Discussionmentioning
confidence: 99%
“…63,64 It is considered that GSH act as cofactor for several protective enzymes that are important in defense mechanism of body from oxidative stress. 33,[65][66][67] There is association between the increase in blood pressure and the oxidative stress. Several clinical investigations showed that serum concentrations of MDA are high in the hypertensive patients than in normal individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It mitigates cardiac hypertrophy by reducing oxidative stress and inactivating c-Jun nuclear kinase (JNK-1) protein in type I diabetes (Adeniyi et al 2015). Naringin ameliorates sodium arsenite-induced renal and hepatic toxicity in rats by modulating the activities of KIM-1, caspase-3, TGF-β and TNF-α (Adil et al 2015). Naringin ameliorates cognitive deficits via oxidative stress, proinflammatory factors and the PPARγ signaling pathway in a type 2 diabetic rat model (Qi et al 2015).…”
Section: Introductionmentioning
confidence: 98%